Quranic Foundations of Maqasid Shariah in the Design of Islamic-Compliant Hotel Services in Malaysia - Rahman, Siti Nur Husna Abd; Azli, Rafidah Mohd; Zhaffar, Nursafra Mohd; Babge, Siti Nadiah Binti (Universitas Muhammadiyah Surakarta, 2025)
This article examines the Quranic foundations of Maqasid Shariah and their relevance to the design of Islamic-compliant hotel services in Malaysia. In response to the growing demand for Shariah-compliant hospitality among Muslim travelers, there is an urgent need for service models that integrate religious principles with customer expectations. The study employs a qualitative thematic analysis of selected Quranic verses that represent the five essential objectives of Maqasid Shariah: the preservation of religion, life, intellect, lineage, and property. These objectives are explored in relation to their operational implications within hotel services such as cleanliness, privacy, ethical marketing, worship facilities, and food preparation. The findings demonstrate that Quranic guidance provides a holistic ethical framework capable of shaping spiritually meaningful and sustainable hotel management models. This study offers valuable insights for policymakers, hoteliers, and Shariah scholars seeking to harmonize spiritual authenticity with contemporary hospitality practices in Malaysia.